2021
DOI: 10.3847/1538-4357/ac013d
|View full text |Cite
|
Sign up to set email alerts
|

Circumnuclear Multi-phase Gas in Circinus Galaxy IV: Absorption Owing to High-J CO Rotational Transitions

Abstract: We studied the absorption features of CO lines against the continuum originating from the heated dust in the obscuring tori around active galactic nuclei (AGNs). We investigated the formation of absorption lines corresponding to the CO rotational transitions using three-dimensional non-LTE line transfer simulations considering the dust thermal emission. As in Papers I–III of this series, we performed post-processed radiative transfer calculations using the “radiation-driven fountain model” (Wada et al. 2016), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 51 publications
3
14
4
Order By: Relevance
“…The observed spectrum and the best-fit model folded with the energy responses of the Circinus galaxy are plotted in Figure A2. We obtain the best-fit inclination angle of ∼87 • , which is consistent with the previous studies, in which the infrared SED, molecular lines in radio, and X-ray continuum spectra are compared with observed ones (Wada et al 2016;Izumi et al 2018;Uzuo et al 2021;Buchner et al 2021). Our model gives a reasonably good description of observed spectrum except the intensities of the emission lines.…”
Section: A2 X-ray Spectrum: Comparison With Circinus Galaxysupporting
confidence: 89%
See 1 more Smart Citation
“…The observed spectrum and the best-fit model folded with the energy responses of the Circinus galaxy are plotted in Figure A2. We obtain the best-fit inclination angle of ∼87 • , which is consistent with the previous studies, in which the infrared SED, molecular lines in radio, and X-ray continuum spectra are compared with observed ones (Wada et al 2016;Izumi et al 2018;Uzuo et al 2021;Buchner et al 2021). Our model gives a reasonably good description of observed spectrum except the intensities of the emission lines.…”
Section: A2 X-ray Spectrum: Comparison With Circinus Galaxysupporting
confidence: 89%
“…Wada et al (2016) applied this radiation-driven fountain model to the Circinus galaxy, which is one of the closest (4.2 Mpc: Freeman et al 1977) type-2 AGN. The model is consistent with several observed features, such as the infrared spectral energy distribution (SED, Wada et al 2016), the dynamics of atomic/molecular gas (Wada et al 2018a;Izumi et al 2018;Uzuo et al 2021), distribution of ionized gas in the NLR (Wada et al 2018b), and broadband X-ray spectra (Buchner et al 2021). Mizumoto et al (2019) also suggested that this kind of dust driven wind may play an important role to the warm absorber acceleration.…”
Section: Introductionsupporting
confidence: 82%
“…The radiation-driven fountain model (Wada et al 2016) suggested a picture that AGN tori are naturally formed by gas circulation around the AGN, and this picture is consistent with multiwavelength observations of low luminosity AGNs, such as the Circinus galaxy (Wada et al 2018a(Wada et al , 2018bIzumi et al 2018;Buchner et al 2021;Ogawa et al 2022). However, these previous studies have not directly verified the gas circulation inside the torus (see also Uzuo et al 2021). In this paper, we propose that CO rovibrational absorption lines can be used to infer the internal motion of the molecular tori and focus on the following four questions: (1) What is the source of continuum radiation at the back of the CO absorption gas in near-infrared observations, especially at the wavelength 4.7 μm?…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, we conclude that CO rovibrational absorption lines can be detected in only the case with inclination angles θ obs = 50 − 80 • , but the detectability of outflow and inflow components depends on the azimuthal angles. (in Appendix A, we discuss differences in observational conditions between our results in the nearinfrared wavelength with a previous theoretical study in the submillimeter wavelengths (Uzuo et al 2021)).…”
Section: Conditions For Detecting Co Absorption Linesmentioning
confidence: 74%
“…We can use molecular absorption lines to know the physical condition of the molecular gas on the line of sight. Uzuo et al (2021) investigated the CO rotational absorption lines in submillimeter wavelength based on the model. The detected CO absorption line profiles for the rotational levels J = 7-6 or higher were affected by those of the CO emission lines, especially if the beam size was not fine enough, and it was difficult to derive the kinematics and level population of the molecular gas inside the torus.…”
Section: Introductionmentioning
confidence: 99%